Revisiting the penetration of Islam in the Philippines and its implication for the development of Muslim institutions: Pengkajian semula tentang penetrasi Islam di Filipina dan kesannya terhadap pembangunan institusi Islam - Gamon, Alizaman Dumangcag; Tagoranao, Mariam Saidona (International Islamic University Malaysia, 2019)
This study discusses the penetration of Islam in the Philippines, particularly the third wave of its expansion, which was brought by Sufi missionaries. It reinstates the historical relevance of Sufi ideas and approaches due to its contemporary relevance to the concept of social co-existence. The rational, intellectual and philosophical dimension of Islam is manifested in the cultural and traditional life of Muslim communities. The study also analyzes the impact of Muslim struggle for the development of Islamic institutions in the context of the secular state. The ongoing, unsettled debate between Islamic and government approaches to peace and development in Mindanao and Sulu continues unabated. Over the years, reforms were introduced, but in their midst, evidence of government biases and prejudices with regards to Islamic institutions have surfaced. Muslim leaders and intellectuals responded in the context of historical rights and freedom, but those views were often questioned as they are presumed to be incompatible with the national agenda for national unity. It was very recently that this incompatibility was readdressed giving support to having lasting peace and justice in Mindanao. The study argues that there have been substantial state-sponsored reforms which may contribute to the gradual advancement of Muslim communities. Though the path for the passage of Muslim concerns within the given condition is fragile and open to challenges, the study recognizes the prominence of inter-civilizational dialogue, from which the universal values of humanity will be embraced by both Muslim and nonMuslim policy makers. In addition, Muslim and non-Muslim communities in the Philippines need to embrace the universal principle of humanity and coexistence due to its relevance to the political stability and economic growth in the country.